Do Workers Speak Up When Feeling Job Insecure? Examining Workers' Response to Precarity During the COVID-19 Pandemic. Issue 1 (February 2023) - Rho, Hye Jin; Riordan, Christine; Ibsen, Christian Lyhne; Lamare, J. Ryan; Tapia, Maite
The COVID-19 pandemic inflicted unprecedented precarity upon workers, including concerns about job insecurity. We examine whether workers respond to job insecurity with voice, and assess the role of unions, managers, and employment arrangements in this relationship. Analyses of an original 2020 survey representative of Illinois and Michigan workers show that job insecurity is not significantly associated with voice. Further, while we find that union membership and confidence in organized labor are positively associated with voice, insecure workers are less likely to speak up than secure workers as confidence in organized labor increases. Last, we find that insecure nonstandard workers are less likely to use voice than their secure counterparts.